Tracked Changes. Aerospace series. Cables, electrical, single and multicore for general purpose. Operating temperatures between -55 °C and 200 °C. MNA (1 core), MNB (pair), MNC (3 cores), MND (4 cores), cables family. Silver-plated copper screened (spiral) and jacketed, UV laser printable. Product standard Part 012, (30th May 2022) - British Standards Institution,
No abstract available